ASP (Application service provider) configuration handbook - Palmatier, Gary. (Rockland, MA : Syngress Pub., 2001)
Understanding ASPs: The new Internet business. Application Service Providers (ASPs) appeal to small businesses by offering a wide variety of web-hosted software programs including e-commerce, communications, project management, financial, word processing and human resourse applications. ASPs offer inexpensive use of software and the ability to share access among people in different locations. There is a huge buzz in the computing industry about ASPs and many ISPs (Internet Service Providers) are gearing up to become ASPs. These companies are in need of a guide - this is the first book to focus on how a company can become an ASP. ASP Configuration Handbook: A Guide for ISPs covers all the business issues surrounding the transformation of an Internet Service Provider to an Application Service Provider, as well as the technical issues associated with offering applications to customers.
Includes index.
At head of title: Syngress.
Keywords: Application service providers; Web servers; Internet programming; Electronic books